2012
DOI: 10.1002/adma.201201442
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic Hydrogels: One‐Step Formation of Multiscale Soft Materials

Abstract: The one-step, continuous formation of mosaic hydrogel sheets is presented. A microfluidic device allows controllable incorporation of secondary biopolymers within a flowing biopolymer sheet followed by a cross-linking step that retains the microscale composition. Information is encoded; mosaic stiffness and diffusivity patterns are created; tessellations are populated with biomolecules, microparticles and viable primary cells; and 3D soft material assemblies are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 55 publications
1
108
0
2
Order By: Relevance
“…However, alginate by itself negatively impacts collagen type one deposition from dermal fibroblasts, potentially making them a non-ideal polymer for skin substitutes[80]. Alginate has been largely considered an ideal polymer for skin printers, devices that seed skin cells onto prefabricated biodegradable scaffolds, due to its ionic cross-linking mechanism[81,82]. Skin printer technology will inevitably advance and thus the use of alginate in skin substitutes will increase.…”
Section: Components Of a Skin Substitutementioning
confidence: 99%
See 1 more Smart Citation
“…However, alginate by itself negatively impacts collagen type one deposition from dermal fibroblasts, potentially making them a non-ideal polymer for skin substitutes[80]. Alginate has been largely considered an ideal polymer for skin printers, devices that seed skin cells onto prefabricated biodegradable scaffolds, due to its ionic cross-linking mechanism[81,82]. Skin printer technology will inevitably advance and thus the use of alginate in skin substitutes will increase.…”
Section: Components Of a Skin Substitutementioning
confidence: 99%
“…Due to the novelty of this emerging technology, most of these methods have not been tested specifically for skin substitutes, yet one form of 3D printing using laser printing has been proven to be effective providing initial evidence of skin regeneration in in vivo mouse models[183,184]. The use of microfluidics has also been used with preliminary positive evidence for skin substitutes, however further research must be completed before any conclusions are to be made[185,186]. Other 3D printing methods have previously been compared and contrasted in current literature and will not be repeated here[182,187], but it is important to address the overall limitations of this newer technology.…”
Section: Creating Skin Substitutesmentioning
confidence: 99%
“…Moreover, it has been shown that using the so-called multilayermicrofluidic devices, mosaic hydrogels with a well-defined spatial composition of materials, cells or pores can be prepared. (Leng, et al, 2012) Based on the oligonucleotide pairs complementarity principle, gel interfaces can be specifically assembled. (Qi, et al, 2013;Deschner, et al, 2014) Setting the spatial/surface presentation of the complementary sequences in the different units allows the formation of controlled assemblies.…”
Section: Specific Assemblingmentioning
confidence: 99%
“…they lack vascularization and few feature melanocytes) and not all approaches are amenable to higherthroughput applications. Fortunately, these challenges are known and are being addressed by a burgeoning field that has yet to show its full potential [5,6]. Table 1 summarizes recent bioprinting approaches relevant to skin production and the cell viability associated with each.…”
mentioning
confidence: 98%